THE EFFECT OF INVESTMENT KNOWLEDGE, RETURN, AND SOCIAL MEDIA ON CAPITAL MARKET INVESTMENT AND THE PROGRESS OF THE MILLENNIUM GENERATION IN THE JABODETABEK REGION - Andini Nurwulandari; Hasanudin Hasanudin; Raihan Raihan (SEAN Institute, 2022)
The purpose of this study was to determine the effect of investment knowledge, return and social media on investment interest and to determine the role of technological advances in moderating the relationship between investment knowledge, return and social media on investment interest. The population of this research is the millennial generation investors who live in Greater Jakarta. Data were collected as many as 140 respondents and processed with IBM AMOS v22 software. The results of this study indicate that investment knowledge, returns and social media have a significant effect on investment interest in the capital market in the millennial generation in Jabodetabek and technological advances can moderate the relationship between investment knowledge, return and social media on investment interest in the capital market in the millennial generation in Jabodetabek